Integrating Disaster Risk Reduction and Environmental Care in Junior Secondary Education: A Systematic Literature Review of Educational Strategies and Attitudes - Fandi, Real; Nasrul, Nasrul; Adumiranti, Yuninda; Nurohman, Sabar (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2025)
This study aims to analyze the Integration of Disaster Risk Reduction and Environmental Concern in Junior High School Education against several existing scientific literature studies. The type of research used in this study is Systematic Literature Review with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method by looking at the inclusion and exclusion criteria. There are 132 articles that have been obtained through the keywords disaster risk reduction in secondary school and Junior High Environmental Attitudes, Screening 83 articles, Eligible 59 Articles, and there are 5 articles that will be reviewed according to the predetermined research topics. The results of this study indicate that the integration of disaster risk reduction and environmental concern at the junior high school level is carried out through various approaches, including social values, environmental ethics, and active student participation. The real-life activity-based approach and visual media have proven effective in increasing students' awareness of the impacts of environmental damage and the importance of collective action. In addition, child-based education and the application of the principles of gender equality and social inclusiveness strengthen students' understanding of their role in climate change adaptation and sustainable disaster mitigation.